PENGARUH TINGKAT SUKU BUNGA BI TERHADAP INDEKS HARGA SAHAM SEKTOR PERBANKAN DI BURSA EFEK INDONESIA PERIODE 2020–2024 - Harmiyanto Pratama; Marsyah Fauziah; Miftahul Jannah; ulfidah Selfyani4; Yuspikarni Gulo (Universitas Prof.Hazairin,SH Bengkulu, 2026)
ABSTRACT Purpose:This research project intends to analyze how the interest rate set by Bank Indonesia impacts the stock price index of banking companies listed on the Indonesia Stock Exchange between 2020 and 2024. The purpose of this study is to determine if shifts in the primary interest rate act as a notable macroeconomic indicator that affects fluctuations in banking stock prices. Methodology/Approach:This study employs a quantitative approach with a causal research design. The data used are secondary time-series data obtained from official publications of Bank Indonesia and the Indonesia Stock Exchange. The research sample consists of 10 conventional commercial banks selected using a purposive sampling method. Data analysis was conducted using simple linear regression, preceded by descriptive statistical analysis and classical assumption tests. Hypothesis testing was performed using the t-test and coefficient of determination analysis. Results/Findings:The results indicate that Bank Indonesia’s interest rate has a positive but statistically insignificant effect on the banking sector stock price index. Furthermore, the coefficient of determination is relatively low, suggesting that variations in the banking sector stock price index are largely influenced by factors other than the interest rate. Conclusion:The findings imply that, during the 2020–2024 period, changes in Bank Indonesia’s interest rate were not a dominant factor in determining the movement of banking sector stock prices. This suggests that investors may place greater emphasis on other macroeconomic variables or firm-specific fundamentals when making investment decisions in the banking sector.